2014
DOI: 10.1161/circoutcomes.113.000329
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Is the Eyeball Test?

Abstract: Background-In the era of increasing percutaneous treatment options for heart disease, the estimation of surgical risk has become a key factor in selecting optimal treatment strategies. Surgical risk has historically been estimated by physician's subjective assessment and more recently by statistical risk estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…In cardiac surgery, surgeons rarely classified individuals as low risk even when they were 19,37,49 . Surgeons' predictions of mortality in both general and cardiac surgery were good, with most of the AUCs presented in papers being greater than 0⋅7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cardiac surgery, surgeons rarely classified individuals as low risk even when they were 19,37,49 . Surgeons' predictions of mortality in both general and cardiac surgery were good, with most of the AUCs presented in papers being greater than 0⋅7.…”
Section: Discussionmentioning
confidence: 99%
“…Where data were presented, surgeons consistently overestimated mortality risk. It is been suggested that the pessimism in predictions may allow patients to exceed surgeons' expectations (when pessimistic predictions are proven wrong), which is psychologically preferable to patients failing to meet a pre-established expectation 37 . In cardiac surgery, surgeons rarely classified individuals as low risk even when they were 19,37,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The database includes information regarding patient demographics, clinical and laboratory variables, surgical details, and post-operative outcomes, including long-term survival (11,12). Additional clinical, pharmacologic, and echocardiographic variables, that were not included in the database, were extracted from electronic medical records (13).…”
Section: Data Sourcementioning
confidence: 99%
“…In clinical practice, experienced surgeons and cardiologists pragmatically and informally estimate individual risk based on their experience, clinical intuition, and judgment . However, robust research methodology mandates validated assessments that objectively predict the probability that a patient will develop an adverse outcome, so as to allow for appraisal of procedural efficacy.…”
Section: Discussionmentioning
confidence: 99%